Gm614 Protects Germinal Center B Cells From Death by Suppressing Caspase-1 Transcription in Lupus-Prone Mice - He, Youdi; Xu, Ruonan; Zhai, Bing; Zhou, Shan; Wang, Xiaoqian; Wang, Renxi (Frontiers in Immunology, 2020)
Only a few signaling pathways have been reported in germinal center (GC) B-cell proliferation and death. In this study, we showed that a novel uncharacterized Gm614 protein is highly expressed in GC B cells from lupus-prone mice. Critically, ablation of this GC B-cell-specific Gm614 promoted GC B-cell death and mitigation of autoimmune symptoms, whereas overexpression protected GC B cells from death and exacerbated autoimmune symptoms. We demonstrated that mechanistically, nuclear-localized Gm614 reduced caspase-1 expression in GC B cells by binding with caspase-1 promoter to suppress its activation. Our results suggest that Gm614 protects GC B cells from death by suppressing caspase-1 transcription in autoimmune diseases. This may provide some hints for targeting the cell proliferation involved in autoimmune diseases.